Modelling of dissolved oxygen in water affected by the sediment layer - Thành, Lê Minh; Phong, Phạm Hồng; Hùng, Lê Quốc (Vietnam Journal of Chemistry, 2014)
The present paper describes a model that simulates the change in dissolved oxygen concentration at the interface between a polluted sediment layer and the water bulk above. With an assumption was that the oxygen consumption was taken place in only the mud by microorganisms and reductants, and was studied by the Monod equation. The model included diffusion processes of oxygen in the water, in the mud and a process of oxygen exchange at the air-water interface. The model was calibrated, validated by experiments with the determination coefficients (R2) of 0.84 and 0.88, respectively. Sensitivity analysis showed that the most sensitive parameters were initial dissolved oxygen concentration, the maximum oxidation rate and diffusion coefficient of oxygen in water and mud